Ciudad universitaria deportiva-high tech del ciclismo (2020)
The document is directed to urban and architectural development, of sports scenarios, and taking as a focus on a new sports element which is a specialized center for the development of professional cyclists, (high tech of cycling in what is of this special for your skills in your different competences.